ChemInform Abstract: Metal Free One‐Pot Synthesis of α‐Ketoamides from Terminal Alkenes. Issue 40 (October 2015) - Dutta, Sayan; Kotha, Surya Srinivas; Sekar, Govindasamy
Abstract A practical synthesis of α‐ketoamides is accomplished by oxidation of styrenes with a mixture of iodine and IBX and subsequent one‐pot coupling with cyclic secondary amines.